ASSESSMENT OF COGNITIVE FUNCTIONS IN PATIENTS WITH POST-COVIDAL CEREBROASTENIC SYNDROME - Ulugbek D. Shadiev; Gulrona S. Rakhimbaeva (Central Asian Journal of Medicine, 2022)
Aim of the study: We aimed to study the occurrence of cognitive impairment in post-covidal cerebroastenic syndrome in patients with various degrees of severity of COVID-19, to assess the severity of the asthenic syndrome, and develop optimal diagnostic approaches. Materials and methods: The presence of cognitive impairments was assessed based on the clinical symptom questionnaire, the MMSE scale (Mini Mnetal State Exam, Folstein, et al., 1975), and the MoCA test (The Montreal Cognitive Assessment, MoCa, 2005). The severity of asthenic manifestations was determined by ASS (Asthenic State Scale modified by L. D. Malkova and T. G. Chertova, 2014). Conclusions: In patients with post-covidal cerebroastenic syndrome, cognitive impairment was assessed using the MMSE scale. In the main group, 21 people had moderate dementia, 27 people had mild dementia, and 20 people had moderate cognitive impairment. In the control group, positive results were recorded within the standard values. The MoCA test revealed a decrease in cognitive functions in the form of moderate dementia in 23, mild dementia in 26 and moderate cognitive impairment in 19 in the main group. Whereas in the comparison group on the first day of admission to the hospital against the background of intoxication.